A Human Amniotic Membrane Plug to Promote Retinal Breaks Repair and Recurrent Macular Hole Closure. (October 2019) - Rizzo, Stanislao; Caporossi, Tomaso; Tartaro, Ruggero; Finocchio, Lucia; Franco, Fabrizio; Barca, Francesco; Giansanti, Fabrizio
Abstract : Supplemental Digital Content is Available in the Text.